3D analysis of microvasculature in murine liver fibrosis models using synchrotron radiation-based microtomography - Wagner, Willi Linus; Föhst, Sonja; Hock, Jessica; Kim, Yong Ook; Popov, Yury; Schuppan, Detlef; Schladitz, Katja; Redenbach, Claudia; Ackermann, Maximilian (Angiogenesis, 2021)
Cirrhosis describes the development of excess fibrous tissue around regenerative nodules in response to chronic liver injury and usually leads to irreversible organ damage and end-stage liver disease. During the development of cirrhosis, the formation of collagenous scar tissue is paralleled by a reorganization and remodeling of the hepatic vascular system. To date, macrovascular remodeling in various cirrhosis models has been examined using three-dimensional (3D) imaging modalities, while microvascular changes have been studied mainly by two-dimensional (2D) light microscopic and electron microscopic imaging. Here, we report on the application of high-resolution 3D synchrotron radiation-based microtomography (SRμCT) for the study of the sinusoidal and capillary blood vessel system in three murine models of advanced parenchymal and biliary hepatic fibrosis. SRμCT facilitates the characterization of microvascular architecture and identifies features of intussusceptive angiogenesis in progressive liver fibrosis in a non-destructive 3D manner.